Festival Anak Saleh di Desa Leang-leang Kabupaten Maros - Aswar Aswar; Rosmita Rosmita (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
Community service (PkM) is one pillar of Tri Dharma in Higher Education. One form of its realization is cooperation between the regional government and universities in the form of implementing KKN that is sustainable and provides mutual benefit (symbiosis of mutualism). The purpose of this PkM was to improve the competence, morals, and attitude of elementary-school-age children in Leang-Leang village through the implementation of a program titled